E-Learning Integration and Its Impact on MIS Skill Development and Student Engagement - Boumedyen Shannaq (Emerging Science Journal, 2024)
This paper aims to establish the possibilities of incorporating e-learning in the management information system (MIS) for Omani students' improvements. The first purpose was to establish whether there was a relationship between e-learning integration and MIS skill development; the second purpose was to further test whether student engagement moderated the relationship or acted as a mediator between the two constructs; and the third purpose was to consider whether or not instructor proficiency and institutional support had a moderating effect on this relationship. Participants included 420 students and lecturers from Omani universities. The study also supported H1 and revealed that e-learning integration significantly, though moderately, enhanced student readiness, with a mean increase of 0.141 (p=0.002). The study revealed that student engagement can only partially mediate this relationship, with a regression coefficient of 0.051 and a significance level of 0.001. Yet, the expertise level of the instructor did not emerge as a significant moderator in this relationship (β=-0.027, p=0.292), thus resulting in another rejection of H3. On the other hand, institutional support had a direct positive effect on the readiness of the students for e-learning when integrated in teaching activities, thus supporting H4 (β=0.071, p=0.05). The R-square change (âˆ†R² = 0.005) indicates that the use of moderators increases explained variance by a small extent. The following findings can assist policymakers and educators in improving MIS education in Oman by leveraging institutional support for e-learning to enhance skills. Doi: 10.28991/ESJ-2024-SIED1-025 Full Text: PDF